Reversible cerebral vasoconstriction syndrome associated with tetrodotoxin poisoning: A case report. Issue 6 (23rd December 2021) - Kakehi, Eiichi; Matsumoto, Makoto; Taniguchi, Shohei; Akamatsu, Yukinobu; Sakurai, Shigehisa; Hirotani, Akane; Nozaki, Takafumi; Shoji, Keisuke; Adachi, Seiji; Kotani, Kazuhiko; Matsumura, Masami
Abstract: An 81‐year‐old woman with a history of hypertension and Alzheimer's disease presented to the emergency department because of impaired consciousness. Physical examination revealed acute progressive generalized flaccid paralysis, hypertension, respiratory failure, and pupillary dilation. Although the patient did not complain of headache, head magnetic resonance angiography and magnetic resonance imaging showed multifocal segmental cerebral vasospasm and cerebral infarction in the left occipital lobe. Her family reported that although she did not have a license to cook pufferfish, she was in the habit of eating pufferfish. We subsequently detected tetrodotoxin in the patient's urine, and she was diagnosed with tetrodotoxin poisoning. As the symptoms of tetrodotoxin intoxication improved, head magnetic resonance angiography showed the disappearance of the multifocal segmental cerebral vasospasm. The patient's clinical course and imaging findings were consistent with reversible cerebral vasoconstriction syndrome (RCVS). Sympathetic overactivity after tetrodotoxin intoxication possibly caused the development of RCVS, and RCVS could not be ruled out even in the absence of the typical thunderclap headache. Magnetic resonance angiography is a useful modality when performing repeated examinations.